Loss of miR-183/96 alters synaptic strength via presynaptic and postsynaptic mechanisms at a central synapse - Krohs, Constanze; Körber, Christoph; Ebbers, Lena; Altaf, Faiza; Hollje, Giulia; Hoppe, Simone; Dörflinger, Yvette; Prosser, Haydn M.; Nothwang, Hans Gerd (The journal of neuroscience, 2021)
A point mutation in miR-96 causes non-syndromic progressive peripheral hearing loss and alters structure and physiology of the central auditory system. To gain further insight into the functions of microRNAs (miRNAs) within the central auditory system, we investigated constitutive Mir-183/96dko mice of both sexes. In this mouse model, the genomically clustered miR-183 and miR-96 are constitutively deleted. It shows significantly and specifically reduced volumes of auditory hindbrain nuclei, because of decreases in cell number and soma size. Electrophysiological analysis of the calyx of Held synapse in the medial nucleus of the trapezoid body (MNTB) demonstrated strongly altered synaptic transmission in young-adult mice. We observed an increase in quantal content and readily releasable vesicle pool size in the presynapse while the overall morphology of the calyx was unchanged. Detailed analysis of the active zones (AZs) revealed differences in its molecular composition and synaptic vesicle (SV) distribution. Postsynaptically, altered clustering and increased synaptic abundancy of the AMPA receptor subunit GluA1 was observed resulting in an increase in quantal amplitude. Together, these presynaptic and postsynaptic alterations led to a 2-fold increase of the evoked excitatory postsynaptic currents in MNTB neurons. None of these changes were observed in deaf Cldn14ko mice, confirming an on-site role of miR-183 and miR-96 in the auditory hindbrain. Our data suggest that the Mir-183/96 cluster plays a key role for proper synaptic transmission at the calyx of Held and for the development of the auditory hindbrain. - SIGNIFICANCE STATEMENT The calyx of Held is the outstanding model system to study basic synaptic physiology. Yet, genetic factors driving its morphologic and functional maturation are largely unknown. Here, we identify the Mir-183/96 cluster as an important factor to regulate its synaptic strength. Presynaptically, Mir-183/96dko calyces show an increase in release-ready synaptic vesicles (SVs), quantal content and abundance of the proteins Bassoon and Piccolo. Postsynaptically, the quantal size as well as number and size of GluA1 puncta were increased. The two microRNAs (miRNAs) are thus attractive candidates for regulation of synaptic maturation and long-term adaptations to sound levels. Moreover, the different phenotypic outcomes of different types of mutations in the Mir-183 cluster corroborate the requirement of mutation-tailored therapies in patients with hearing loss.
Gesehen am 12.10.2021